Multiculturalidad en las Organizaciones Internacionales. Selección de funcionarios internacionales en la Organización de Naciones Unidas (2019)
International Organizations have an increasingly important role in today’s International Relations. This category includes a huge range of organizations, from intergovernmental organizations to multinational corporations. International Organizations are made up of international functionaries who act in accordance to their cultural codes. These codes are not only determined by their nationalities, but by a long list of other “cultural elements”. Integration and juxtaposition of different cultures within International Organizations is an important factor in their everyday work. The advantages of cultural richness could also be seen as the disadvantages associated to an effective organizational communication. This paper intends to evaluate how the main elements that determine the cultural conformation are integrated in the selection processes of international functionaries, particularly in the United Nations, which is taken as a case study.